2018
DOI: 10.12691/ajnr-6-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nurses' Involvement, Feeling, Perception and Barrier for Practice Breaking Bad News in Jordan

Abstract: Background. Breaking bad news (BBN) is one of the most difficult tasks faced by healthcare providers. In addition, breaking bad news is stressful for both; healthcare providers and patient. Nurses can play an important role in the process of BBN. Whereas, effective communication by critical care nurses improves patients' understanding of their health status and decreases their stress level. Furthermore, effective BBN process requires effective communication skills. Aims. To assess critical care nurses' knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
(40 reference statements)
1
10
1
Order By: Relevance
“…The findings of the current study revealed that Jordanian critical care nurses face many barriers when breaking bad news. The highest mean score for barriers was related to training, similar to the findings of Adebayo et al (2013) and Alkhawaldeh et al (2018) ; this might be due to lack of training and knowledge, unavailability of official curricula, and unavailability of standards or an effective protocol about breaking bad news. Based on the barriers faced by Jordanian nurses and the complexity of this task, adequate skills and knowledge are required to break bad news effectively.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The findings of the current study revealed that Jordanian critical care nurses face many barriers when breaking bad news. The highest mean score for barriers was related to training, similar to the findings of Adebayo et al (2013) and Alkhawaldeh et al (2018) ; this might be due to lack of training and knowledge, unavailability of official curricula, and unavailability of standards or an effective protocol about breaking bad news. Based on the barriers faced by Jordanian nurses and the complexity of this task, adequate skills and knowledge are required to break bad news effectively.…”
Section: Discussionsupporting
confidence: 65%
“…This result was consistent with Warnock and colleagues (2010), who believe that nurses deal with many different cultures and ages, despite their lack of knowledge, while their attention to ethical principles when breaking bad news strengthens their relationships with patients/relatives. However, this finding is not in line with Alkhawaldeh et al (2018), who documented that being involved in this process had strengthened participants' relationships with patients/relatives with the least frequency.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The role of the nurse before BBN is to prepare the patient, family, and environment before BBN. [ 14 - 16 ] Therefore, the nurse must be able to establish a trusting and meaningful relationship with the patient and find out the patient’s wishes. [ 17 , 18 ] In addition, the nurse also has a role in anticipating the patient’s and family’s reactions to the bad news that will be delivered.…”
Section: Resultsmentioning
confidence: 99%